An Efficient Protocol for Model Legume Root Protoplast Isolation and Transformation - Jia, Ning; Zhu, Yali; Xie, Fang (Frontiers in Plant Science, 2018)
Transient gene expression systems using protoplasts have been widely used for rapid functional characterization of genes and high-throughput analysis in many model and crop species. Here, we describe a simplified and highly efﬁcient root protoplast isolation and transient expression system in the model legumes Lotus japonicus and Medicago truncatula. Firstly, we presented an efficient protocol for isolating protoplasts from L. japonicus and M. truncatula roots. We then established an efficient transient expression system in these legumes root protoplasts. Using this protocol, the subcellular localization of two symbiosis related proteins (SYMRK and ERN1) were visualized in the plasma membrane and nuclei, respectively. Collectively, this efficient protoplast isolation and transformation protocol is sufficient for studies on protein subcellular localization, and should be suitable for many other molecular biology applications.